Analisis Kesejahteraan Ekonomi Rumah Tangga Nelayan dan Perilaku Ekonomi Rumah Tangga Nelayan Melalui Moral Ekonomi dan Derajat Kewirausahaan Nelayan Kabupaten Sampang Jawa Timur - Amin Makruf (Universitas 17 Agustus 1945 Surabaya, 2015)
Small fishermen only able to utilize the resources in coastal area with the catch products that tend to decline continually, due to the competition with large ships and the decline of coast resources qualities. Catch products also easy to damage thus weaken their bargain position in sales transaction. In addition to the fish resources the sea zone of Sampang Regency also contains various kinds of resources, both renewal and non-renewal resources, and environmental services, both in the sea and in its coastal area. Sea zone of Sampang Regency is one of zones with the biological diverse and rich of mine and mineral materials and it potential for the development of industrial, tourism, fishery, settlement activities and so forth. Because of the potentials then it needed the presence of economic empowerment for the community in Sampang Regency, through the economic moral and the entrepreneurship level. Population in this research was the 171 fishermen in Sampang Regency of Madura, consisted of 49 fishermen of PEMP members and a number of 122 fishermen of self-fund fishermen. From the testing result on the model in this research, by the Maximum Likelihood Estimation (MLE), the structural equation model (SEM) analysis, the proportional random sampling method and the assistance of software Amos 22, on 140 respondents. The research result indicated that: 1) Economic moral has significant effect on economic behavior. 2) Entrepreneurship level has significant effect on economic behavior. 3) Economic moral has significant effect on fishermen household economic welfare. 4) Entrepreneurship level has significant effect on fishermen household economic welfare. 5) Fishermen economic behavior has significant effect on fishermen household economic welfare. Of the three variables hypothesized as influential on fishermen household economic welfare in this research, whose value largest is the direct relevance between the fishermen entrepreneurship and the fishermen household economic welfare. This case affirms that the fishermen entrepreneurship level is very dominant to influence the fishermen household economic welfare in Sampang Regency of Madura. Key words: economic moral, entrepreneurship level, economic behavior, fishermen economic welfare